Effect of Magnesium Ion on the Radical-Scavenging Rate of Pterostilbene in an Aprotic Medium: Mechanistic Insight into the Antioxidative Reaction of Pterostilbene - Ikuo Nakanishi; Yoshimi Shoji; Kei Ohkubo; Megumi Ueno; Kei Shimoda; Ken-ichiro Matsumoto; Kiyoshi Fukuhara; Hiroki Hamada (MDPI AG, 2022)
Pterostilbene (PTS), a methylated analog of resveratrol (RSV), has recently attracted much attention due to its enhanced bioavailability compared to RSV. However, little is known about the radical-scavenging mechanism of PTS. In this study, we investigated the effect of Mg(ClO4)2 on the scavenging reaction of galvinoxyl radical (GO•) by PTS in acetonitrile (MeCN). GO• was used as a model for reactive oxygen radicals. The second-order rate constant (kH) for the GO•-scavenging reaction by PTS was more than threefold larger than that by RSV, although thermodynamic parameters, such as the relative O-H bond dissociation energies of the phenolic OH groups, ionization potentials, and HOMO energies calculated by the density functional theory are about the same between PTS and RSV. The oxidation peak potential of PTS determined by the cyclic voltammetry in MeCN (0.10 M Bu4NClO4) was also virtually the same as that of RSV. On the other hand, no effect of Mg (ClO4)2 on the kH values was observed for PTS, in contrast to the case for RSV. A kinetic isotope effect of 3.4 was observed when PTS was replaced by a deuterated PTS. These results suggest that a one-step hydrogen-atom transfer from PTS to GO• may be the rate-determining step in MeCN.